STRATEGI KEPALA SEKOLAH DALAM MENGEMBANGKAN MINAT DAN BAKAT KEAGAMAAN PESERTA DIDIK - Anisa Faradila R; Acep Nurlaeli; Abdul Kosim (TABYIN: JURNAL PENDIDIKAN ISLAM, 2025)
The principal's strategy is generally a part of the principal's mandate in carrying out his work, namely planning activities related to schools and students. One of the principal's duties is to develop students' interests and talents. This is important to help the difficulties faced by students in the process of channeling their interests and talents, because students do not know the potential interests that exist within them and lack of support with practical activities in the field. Of course there are many things that school principals can do, such as compiling activity programs, shopping for extracurricular coaches, and targets for developing religious interests and talents. Talent is basically a person's ability to learn in a relatively short time, while interest is a process of paying attention and focusing on something he is interested in with a feeling of pleasure and satisfaction. This study aims to determine the principal's strategy in developing the interests and talents student, to find out the principal's strategy in developing the interests and talents student scholarships. This research uses descriptive qualitative method. Data collection techniques were carried out by means of observation, interviews and documentation. The subjects in the study taken in this study were 1 school principal, 1 vice principal for student affairs, 1slamic spiritual mentor (rohis), and 10 students. The results of the study show that: The strategies carried out by the principal in developing the interests and talents of students are; make plans with the deputy head of student affairs and spiritual mentors to find out the extent of scholarship interests and talents possessed by the students themselves, to provide motivation to students in developing their interests and talents. pay attention to students, and establish cooperation with the parents of the students themselves. Supporting factors in the development of students' talents are support from parents which cannot be separated from school support.